'Having Enough': Students' Understanding of Food Insecurity and Campus Food Pantry Use. Issue 7 (10th November 2019) - Daugherty, Jamie B.; Birnbaum, Matthew; Clark, Alena
ABSTRACT: This narrative inquiry study explored the experiences of three students facing food insecurity and their use of a campus food pantry at a rural four-year public higher education institution the United States. Data collection methods included semi-structured interviews, journaling, and photo elictation. Developing budget priorities, strategic use of the food pantry, and having enough were themes shared by each participant. Implications for findings include creating a dialogue, maximizing resource utilization, and providing support groups.